Winning when Going Global – On the Role of Heritage and Strategic Moves for Internationalization Endeavors of Start-ups - Radu-Andrei Maldea (Junior Management Science (JUMS), 2023)
As the chief subjects for global progress, international new ventures (INVs) are gaining worldwide economic importance at an increasing pace. Most recently, they have received growing attention in the research literature because the validity of existing internationalization theories for has been questioned when used in a new venture setting. So far, prior literature has focused on understanding INV characteristics and the effect that their properties have on the internationalization performance. Aiming to develop a new framework for start-up internationalization, this thesis combines results from a quantitative study on the Strategic Moves of early internationalizing start-ups with results from a literature review on the Heritage of these new ventures. Within the study researching the Strategic Moves, data from 51 European start-ups show the optimal moves start-ups can undertake. The complementary literature review, based on 45 papers from the INV research field, shows what characteristics the ideal Heritage of an INV should consist of. Taken together, the findings construct the Startup Internationalization Framework which establishes the first holistic perspective on start-up internationalization.
Keywords: 650; International new ventures; Early internationalizing start-ups; Internationalization strategy; Market entry; Global management